Crystal structure of 2-benzylamino-4-p-tolyl-6, 7- dihydro-5H-cyclopenta[b]pyridine-3-carbonitrile. (February 2015) - Nagalakshmi, R. A.; Suresh, J.; Maharani, S.; Kumar, R. Ranjith; Lakshman, P. L. Nilantha
No abstract available